The Importance Of Foreign Direct Investments On Economic Development In Transitional Countries: A Case Study Of Kosovo - Halil Kukaj; Faruk B. Ahmeti (European Scientific Journal, ESJ, 2016)
The role of investment, in particularly foreign direct investment (FDI), is regarded as one of the most important contributors of economic growth. The past quarter century has witnessed remarkable growth in FDIs flow all over the world. This is due to the fact that many countries, especially developing countries, see FDI as an important element in their overall strategy for economic development. This paper provides a review of the economic impact of FDI, with specific focus on developing countries particularly Kosovo and ex-Yugoslavian countries in the Balkan Peninsula. FDIs contribute to the economic development of host country in two main ways. They include the augmentation of domestic capital and the enhancement of efficiency through the transfer of new technology, marketing and managerial skills, innovation, and best practices. Secondly, FDI has both benefits and costs, and its impact is determined by the country’s specific conditions in general and the policy environment in particular. This is in terms of the ability to diversify, the level of absorption capacity, targeting of FDI, and the various opportunities for linkages between FDI and domestic investment. The paper aims to clarify the main causes of failure of foreign direct investments in Kosovo and reviles the importance of indicators that majorly has an institutional nature. Neither the amount nor the effects of foreign direct investment were satisfactory. Therefore, the paper reviles that in this aspect, a wide range of actions needs to be made, which is specifically related to government institutions and the business community.